Upaya Pencegahan Resistensi Antibiotik Melalui Edukasi Antibiotik di Klinik Kimia Farma Pramuka Banjarmasin - Catherina Adeline Kurniawan; Fitrian Desmana; Khairunnida Khairunnida; Okta Muthia Sari; Ester Novella br Tobing; Muhammad Andin; Dwi Aulina; Hastuti Hastuti (Jurnal Pelayanan dan Pengabdian Kesehatan untuk Masyarakat, 2026)
Antibiotic resistance is a significant issue in the area of antibiotic use. The rise in antibiotic consumption across various sectors of healthcare and agriculture risks leading to the development of antibiotic resistance. This health education program aims to increase the knowledge of visitors to the Kimia Farma Pramuka Banjarmasin Clinic with information about the dangers of antibiotic resistance, its prevention, and the principles of proper antibiotic use. The health education program utilizes a lecture method. The target participants of this health education program are visitors in the waiting room of the Kimia Farma Pramuka Banjarmasin Clinic on January 16, 2025. The health education materials used are leaflets. The success of the health promotion was evaluated by measuring the participants' knowledge before and after the health education program. This activity was attended by 19 participants and ran smoothly. The results of the measurement of the participants' initial knowledge showed an average score of 34.74%. Then, the participants' final knowledge was measured, with an average score of 90.53%. Conclusion: the knowledge of visitors to the Kimia Farma Pramuka Banjarmasin Clinic increased by 55.79% after education about the dangers of antibiotic resistance, its prevention, and the principles of proper antibiotic use.